Unusual Source of Gastrointestinal Bleed and Endoscopic Management - Choudhary, Narendra S; Bansal, Rinkesh Kumar; Puri, Rajesh; Gupta, Mahesh Kumar; Patil, Gaurav; Shah, Vinit; Nasa, Mukesh; Sud, Randhir (Journal of Digestive Endoscopy, 2018)
Gastrointestinal (GI) bleeding due to jejunal diverticula is very rare. Capsule endoscopy is a useful diagnostic tool for localizing the bleeding site, but single‑balloon enteroscopy is a good therapeutic modality for the management. Here, we report two cases, in whom the cause of GI bleeding was jejunal diverticula and they managed successfully with endoscopic management.
Keywords: Hemoclip; jejunal diverticula; melena